The degree to which teachers practice the skill of providing a safe classroom environment in light of the spread of the new Corona virus (Covid-19) from their point of view (A field study on a sample of teachers in the first cycle of basic education in T - غانم, ثناء; مبيض, مهند; عمران, ديما (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of this research was to identify the degree to which teachers practice the skill of providing a safe classroom environment in light of the spread of the new Corona virus (Covid-19) from their point of view, as well as explore whether there are statistically significant differences between the averages of teachers’scores on the questionnaire on the degree to which teachers practice the skill of providing a safe classroom environment in light of the spread of the new Corona virus (Covid-19) according to the school type variables (public / private) and educational experience. The sample of the research consisted of (145) teachers in Tartous city. The researcher has prepared a questionnaire on the degree to which teachers practice the skill of providing a safe classroom environment consisting of (34) items, and distributed on three axes: (the physical classroom environment, the psychological classroom environment, and the social class environment), the researcher followed descriptive approach to achieve the objectives of the research, and Search reached for several results: - The degree to which teachers practice the skill of providing a safe classroom environment in light of the spread of the new Corona virus (Covid-19) was high, from their viewpoint. - There is no statistically significant difference between the teachers' average scores on the questionnaire on the degree of teachers' practice of the skill of providing a safe classroom environment in light of the spread of the new Corona virus (Covid-19) according to the school type variable (public / private) and the educational experience variable.